Sri Lanka is a hot spot for illegal transnational trading of biodiversity and wildlife materials from South Asian region - Azam, A.W.M.; Jayasuriya, K.M.G.G.; Musthafa, M.M.; Marikar, F.M.M.T. (Springer Verlag (Germany), 2016)
Trafficking of biodiversity materials have been regarded as a major threat to the ecological balance on earth and Sri Lanka is not spared on that too. This paper describes the protocol in the context of illicit trade in biodiversity and wildlife materials trade products across Sri Lanka during the period of 1992–2009. Further this paper highlights which can be effective to counter attack and save the illegal transnational trading and how the region could approach a coordinated implementation of those key provisions. Details of the current illegal biodiversity during that period was highlighted and Sri Lankan Customs great effort on protect the countries pride on conservation of biodiversity and weak points of illegal transaction was pointed out clearly with remedies.